1993
DOI: 10.1002/ijc.2910530614
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of GD2 ganglioside in patients with retinoblastoma

Abstract: Retinoblastoma is a rare tumor of the young child with an intraocular localization that leads to certain problems of diagnosis. With the aim of defining a biochemical marker-which is still lacking for this disease--the gangliosides of a pool of fresh retinoblastoma tumors were analyzed. The ganglioside pattern was shown to have GM3, GM2, GM I, GD3, GD2, GD I b and GTlb as the major components. The occurrence of a high concentration of GD2 in the tumors led us to investigate the possibility of changes in the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…As tumor cells proliferate, gangliosides are shed into their local microenvironment both in vitro and in vivo (1)(2)(3)(4), particularly by tumors of neuroectodermal origin. Many different molecular species are shed, and generally they reflect the ganglioside complement of the tumor cells.…”
Section: Inhibition Of Tlr Activation and Up-regulation Of Il-1r-assomentioning
confidence: 99%
See 1 more Smart Citation
“…As tumor cells proliferate, gangliosides are shed into their local microenvironment both in vitro and in vivo (1)(2)(3)(4), particularly by tumors of neuroectodermal origin. Many different molecular species are shed, and generally they reflect the ganglioside complement of the tumor cells.…”
Section: Inhibition Of Tlr Activation and Up-regulation Of Il-1r-assomentioning
confidence: 99%
“…We and others have previously reported that pretreatment with gangliosides inhibits differentiation and activation of APCs (dendritic cells (DC) 4 and monocytes) following stimulation with LPS, including failure to up-regulate expression of proinflammatory cytokines and cell surface costimulatory molecules CD80 and CD86 (12, 19 -21).…”
Section: Inhibition Of Tlr Activation and Up-regulation Of Il-1r-assomentioning
confidence: 99%
“…Eighty-three subjects (25 healthy, 27 with atrophic AMD and 31 with exudative AMD) were selected on the basis of fundus and optical coherence tomography tests to diagnose the existence of AMD and to determine its form (atrophic or exudative). Using a medical history questionnaire, we excluded patients whose GG levels and/or profile could be abnormal, on the basis of current knowledge (neurodegenerative disease [11,14], diabetes [19,20], history of cancer [7,8,9,10]). For each patient included, 5 ml of blood was collected on anticoagulant (EDTA).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, several studies have reported on the role of circulating GGs as biomarkers of some diseases. Elevated levels of serum GGs have been measured in patients with colorectal cancer [7], and a specific GG class, disialoganglioside 2 (GD2), has been found in the serum of patients with neuroblastoma [8,9] and retinoblastoma [10]. Changes in the distribution of serum GGs have also been described during multiple sclerosis attacks [11].…”
Section: Introductionmentioning
confidence: 99%
“…Tumour cells, particularly tumours of neuroectodermal cell origin, express high levels of gangliosides and shed them in the microenvironment in vitro and in vivo. [1][2][3] Clinically, increased levels of tumourderived circulating gangliosides correlate with disease status and are predictive of more rapid disease progression in patients with advanced stage neuroblastoma, suggesting that gangliosides may play a role in tumour development and progression. 4,5 In support of this hypothesis, tumourderived gangliosides have been shown to modulate growth factor signalling of normal cells in the tumour microenvironment such as fibroblasts and vascular endothelial cells that may promote tumour growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%